Electron spectroscopy and dynamics of HBr around the Br 1s−1 threshold. Issue 46 (23rd November 2020) - Boudjemia, Nacer; Jänkälä, Kari; Püttner, Ralph; Marchenko, Tatiana; Travnikova, Oksana; Guillemin, Renaud; Journel, Loïc; Ismail, Iyas; Koulentianos, Dimitris; Kosugi, Satoshi; Azuma, Yoshiro; Patanen, Minna; et al.
Abstract : A comprehensive electron spectroscopic study combined with partial electron yield measurements around the Br 1s ionization threshold of HBr at ≅13.482 keV is reported. Abstract : A comprehensive electron spectroscopic study combined with partial electron yield measurements around the Br 1s ionization threshold of HBr at ≅13.482 keV is reported. In detail, the Br 1s −1 X-ray absorption spectrum, the 1s −1 photoelectron spectrum as well as the normal and resonant KLL Auger spectra are presented. Moreover, the L-shell Auger spectra measured with photon energies below and above the Br 1s −1 ionization energy as well as on top of the Br 1s −1 σ* resonance are shown. The latter two Auger spectra represent the second step of the decay cascade subsequent to producing a Br 1s −1 core hole. The measurements provide information on the electron and nuclear dynamics of deep core-excited states of HBr on the femtosecond timescale. From the different spectra the lifetime broadening of the Br 1s −1 single core-hole state as well as of the Br(2s −2, 2s −1 2p −1, 2p −2 )  double core-hole states are extracted and discussed. The slope of the strongly dissociative HBr 2p −2 σ* potential energy curve is found to be about −13.60 eV Å −1 . The interpretation of the experimental data, and in particular the assignment of the spectral features in the KLL and L-shell Auger spectra, is supported by relativistic calculations for HBr molecule and atomic Br.